Game „Escape room“ as innovative teaching material - Đorđević, Ana (Norma, 2025)
Modern teaching requires students to be active participants in their education. One of the challenges that teachers face is motivating students to learn. A game, as an activity that is close to children, can be an excellent didactic tool if it is adapted to the goals of teaching and learning. Escape room is a popular game based on teamwork, discovering clues and solving puzzles in order to escape from a locked room in a limited amount of time, with a certain dose of mystery and immersion into the story. It can be created in a room, but also in a digital form. Teachers around the world have recognized the possibilities of applying this game in education and its benefits. The aim of this paper is to present the concept of the game itself, as well as those benefits if it is used correctly in teaching, relying on literature. In addition, it will be given examples of using this game in classes that are presented in the relevant literature. Besides requiring cooperation and teamwork since it is played in a group, it also affects the development of skills such as problem solving, logical and critical thinking, creativity, data analysis. Also, due to the story that is an integral part of this game, it develops imagination, but it can also imitate real-life situations and require students to navigate them. What could be an obstacle for teachers to use it in their classes is the time needed to create the game and puzzles, as well as the resources that are most often provided by the teachers themselves. An insight into the relevant literature led to the conclusion that this topic has not been sufficiently researched in our country, despite all the potential that this game offers, and this paper can be a starting point for future research.